Pengaruh Metode Pembelajaran dan Gaya Kognitif Terhadap Kemampuan Menulis - - Fahrurrozi (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: The objective of this research was to determine the effects of quantum teaching method on the student’s writing ability by considering the learner’s cognitive style. The study was conducted at the PGSD Study Program of FIP Jakarta State University. The study employed the experimental method with 2 x 2 factorial designs. The sample of the study was one-hundred and four-semester IV students, selected from both study programs by employing the multi-stage random sampling technique. The data were analyzed by using a two way ANOVA. Further analysis carried out by employing the Tuckey test shows that the field dependent cognitive style students that were taught by using quantum teaching method gained higher learning results in writing than the learning results of the students who followed the expository teaching method. Furthermore, The writing ability of the students with field independent cognitive style  that were taught by the quantum teaching method was insignificantly different from that of the students that followed the expository teaching  method. Both teaching method and cognitive style affect students’ writing ability and that there is an interaction effect of the teaching methods and the student’s cognitive style on the students’ writing ability.